A putative homologue of CDC20/CDH1 in the malaria parasite is essential for male gamete development - Guttery, David S.; Ferguson, David J. P.; Poulin, Benoit; Xu, Zhengyao; Straschil, Ursula; Klop, Onny; Solyakov, Lev; Sandrini, Sara M.; Brady, Declan; Nieduszynski, Conrad A.; Janse, Chris J.; Holder, Anthony A.; et al. (Public Library of Science, 2012)
Cell-cycle progression is governed by a series of essential regulatory proteins. Two major regulators are cell-division cycle protein 20 (CDC20) and its homologue, CDC20 homologue 1 (CDH1), which activate the anaphase-promoting complex/cyclosome (APC/C) in mitosis, and facilitate degradation of mitotic APC/C substrates. The malaria parasite, Plasmodium, is a haploid organism which, during its life-cycle undergoes two stages of mitosis; one associated with asexual multiplication and the other with male gametogenesis. Cell-cycle regulation and DNA replication in Plasmodium was recently shown to be dependent on the activity of a number of protein kinases. However, the function of cell division cycle proteins that are also involved in this process, such as CDC20 and CDH1 is totally unknown. Here we examine the role of a putative CDC20/CDH1 in the rodent malaria Plasmodium berghei (Pb) using reverse genetics. Phylogenetic analysis identified a single putative Plasmodium CDC20/CDH1 homologue (termed CDC20 for simplicity) suggesting that Plasmodium APC/C has only one regulator. In our genetic approach to delete the endogenous cdc20 gene of P. berghei, we demonstrate that PbCDC20 plays a vital role in male gametogenesis, but is not essential for mitosis in the asexual blood stage. Furthermore, qRT-PCR analysis in parasite lines with deletions of two kinase genes involved in male sexual development (map2 and cdpk4), showed a significant increase in cdc20 transcription in activated gametocytes. DNA replication and ultra structural analyses of cdc20 and map2 mutants showed similar blockage of nuclear division at the nuclear spindle/kinetochore stage. CDC20 was phosphorylated in asexual and sexual stages, but the level of modification was higher in activated gametocytes and ookinetes. Changes in global protein phosphorylation patterns in the Δcdc20 mutant parasites were largely different from those observed in the Δmap2 mutant. This suggests that CDC20 and MAP2 are both likely to play independent but vital roles in male gametogenesis.